Subclinical mastitis in New Zealand grazing dairy ewes 1: Prevalence and risk factors - Chambers, Greg; Lawrence, Kevin; Grinberg, Alex; Velathanthiri, Niluka; Ridler, Anne; Laven, Richard (Journal of dairy science, 2025)
Our objectives were to describe subclinical mastitis and identify its risk factors among grazing dairy ewes in New Zealand. Gland-level milk samples were collected from ∼15 randomly selected ewes on each of 20 dairy sheep farms at early, mid, and late lactation in a repeated cross-sectional study. California Mastitis Tests (CMT; measured on a scale of 0, trace, 1, 2, or 3) and aerobic bacterial culture were performed at the gland level, and SCC at the ewe level using composite milk samples. Subclinical mastitis was defined at the ewe level as having 1 or 2 bacteriologically positive glands and SCC >500 × 103 cells/mL or a CMT score ≥1 (or both). Milk samples were collected from 893 ewes, and complete subclinical mastitis data were available for 856 ewes. Median (range) SCC was 128,000 (2,000–34,953,000) cells/mL. A CMT score ≥1 in one or both glands was found in 21.2% of ewes. Bacteria were isolated from 5.5% of glands, with the most common species being non-aureus staphylococci (4.0% of glands) and Staphylococcus aureus (0.6% of glands). The prevalence of subclinical mastitis was 6.4% (95% CI = 4.6%–8.7%) and was not strongly clustered within farms (intraclass correlation coefficient = 0.04). Ewes with moderate or severe teat end hyperkeratosis had 6.4 times higher odds of subclinical mastitis than ewes with no or mild hyperkeratosis, and ewes with asymmetric udders had 2.3 times higher odds. The odds declined across the 3 visits. The prevalence was low compared with studies of more intensively farmed ewes in the northern hemisphere, but the bacterial causes were consistent. Subclinical mastitis management should be focused at the ewe level before the farm level, given the weak clustering within farms. When addressing or preventing a subclinical mastitis challenge, producers should consider teat end hyperkeratosis and udder asymmetry as simple visual screening tools but not rely on them alone to identify ewes at risk of subclinical mastitis. We present new information for New Zealand grazing dairy ewes, examine udder asymmetry as a diagnostic tool for subclinical mastitis, and show that, although prevalence was lower in New Zealand, the dominant pathogens are consistent, supporting the broader relevance of these findings to international mastitis control, albeit with adaptations for pasture-based systems.